Learning styles of Zahedan dental students by using the VARK model in 2019-2020 - Marieh Honarmand; Ghazal Koochaknejad; Alireza Hajihosseini (Mashhad University of Medical Sciences, 2020)
Background: A learning style is a unique way of acquiring knowledge and skills obtained through study and experience. It is one of the most effective factors in learning, as well as the most important goal of an educational system. This study aimed to analyze the learning style of Zahedan general dentistry students in 2019-2020. Methods: In this descriptive-analytical cross-sectional study, the research population included all dentistry students of Zahedan University of Medical Sciences who were selected by using the enumeration method. The VARK Questionnaire was employed to collect data and the results were then analyzed through the chi-square and ANOVA test in SPSS 23. (P < 0.05 was considered significant) Results: Eighty-two percent of the students were unimodal learners and the aural style with a frequency of %43.32 was the preferred method among participants. Regarding the multimodal approaches, aural-read/write style with a frequency of %6.8 was the most common method. The results showed no significant relationships between the test variables and the learning style (p ≥0.05). Conclusion: According to the results of the present research, the unimodal style was the most common learning style. In addition, the aural style was the most preferred learning style. None of the studied variables, even the educational stage, had any effects on the preferred learning style. Finally, the aural style was identified as the preferred learning style in all groups.